Production of Microsclerotia From Entomopathogenic Fungi and Use in Maize Seed Coating as Delivery for Biocontrol Against Fusarium graminearum - Rivas-Franco, Federico; Hampton, John G.; Altier, Nora A.; Swaminathan, Jayanthi; Rostás, Michael; Wessman, Per; Saville, David J.; Jackson, Trevor A.; Jackson, Mark A.; Glare, Travis R. (Frontiers in Sustainable Food Systems, 2020)
The commercial use of the entomopathogenic fungi Metarhizium spp. in biopesticides has more gained interest since the discovery that several species of this genus are able to colonize roots. The extent of root colonization and the nature of the plant - fungus association resembles those of mycorrhizae since stimulation of secondary roots, plant growth promotion, nutrient availability for plant uptake, as well as antagonism towards plant pathogens and even priming of induced plant resistance have been attributed to the presence of Metarhizium spp. In general, commercial products with Metarhizium are formulated based on conidia for insect pest control. The process of mass production, harvesting and formulation of infective conidia can be detrimental for conidial viability. Entomopathogenic fungi such as Metarhizium spp. are able to produce high concentrations of resistant structures, known as microsclerotia, when grown in liquid media. Microsclerotia are desiccation tolerant, with excellent storage stability, and are capable of producing high quantities of infective conidia after rehydration. The aim of this study was to evaluate microsclerotia production by different isolates of Metarhizium spp. and determine the effect of microsclerotia coated onto maize seeds on plant growth in the presence of soil-borne pathogen Fusarium graminearum. On average, approximately 1 x 105 microsclerotia/mL were produced by selected isolates of M. anisopliae (A1080 and F672) and Metarhizium robertsii (F447). Microsclerotia were formulated as granules with diatomaceous earth and used for seed coating, after which propagules produced around 106 CFUs per gram of seeds. In the presence of the plant pathogen, maize control plants had the lowest growth, while plants treated with the Metarhizium microsclerotia had significantly greater growth than the control plants. Hyphae were observed growing on and in root tissues in all the Metarhizium spp. treatments but not in samples from control plants. Hyphal penetration points on roots were observed one month after sowing, indicating the fungi were colonizing roots as endophytes. The results obtained indicate that microsclerotia can be coated onto seeds, providing plant protection against soil plant pathogens and a method to establish Metarhizium in the ecto- and endo-rhizosphere of maize roots, allowing the persistence of this biocontrol agent.